(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
This paper analysis the immediate roof (IR) stability by the deformation criteria for new room-andpillar mining technology with modern machines in “Estonia” mine. The new mining technology based on a blasting method to move from packaged to emulsion explosives, from 2.0 m to 4.0 m boreholes (FRANZ SCHELL machine) and on new undercutting (SMAG machine) method. With such equipped new technology the entry advance rates reached 3.8 m. As a result of such greater advance rates the situations with unsupported room length up to 5.5 m with decreasing the stability of IR can be expected. The analysis of IR stability based on an in-site underground testing by the leaving bench-mark stations and convergence measurements. The main targets of this study to determine the main parameters for supported/unsupported IR deformation in areas with great entry advance rates and risk analysis concept elaboration.